Transpedicular decancellation osteotomy in the treatment of posttuberculous kyphosis - KÜÇÜKDURMAZ, FATİH; BEZER, MURAT (LIPPINCOTT WILLIAMS & WILKINS, 2007)
Objective: Although the transpedicular decancellation osteotomy is a salvage technique for reconstruction of complex spinal deformities, it is not a procedure used exclusively for patients with kyphosis occurring as a sequel of treated tuberculosis. In this study, 16 adult patients with kyphosis underwent transpedicular decancellation osteotomy between 1993 and 1999. Pain, kyphosis angle, sagittal balance, and functional and neurologic status were the main parameters used for the clinical and radiologic assessment. Methods: Sixteen patients with angular kyphotic deformity underwent transpedicular decancellation osteotomy between 1993 and 1999 with at least 5 years of follow-up. There were 6 male and 10 female patients with a mean age of 51.0. The radiologic involvement included the angle of kyphosis and plumb line on the anteroposterior and lateral radiographs. The preoperative and postoperative clinical assessment was performed by the using Oswestry Disability Index. All patients were asked to rate their preoperative and postoperative pain measurement using a pain visual analog scale. Fusion was evaluated on flexion-extension lateral radiographs. Results: There were significant corrections in the kyphosis angle and the sagittal balance whereas no radiologic correction loss was observed in any of the patients during follow-ups. When the preoperative and the last follow-up pain visual analog scale and Oswestry Disability Index scores were compared, decrease was documented in both of them. Bony fusion was achieved in all patients and no neurologic complications were detected. Conclusions: The transpedicular decancellation osteotomy effectively corrected the sagittal balance and improved pain and functional status. It was a safe and reliable technique in the treatment of posttuberculosis kyphosis.
Keywords: transpedicular decancellation osteotomy; tuberculosis; kyphosis; sagittal offset; PEDICLE SUBTRACTION OSTEOTOMY; SPINAL TUBERCULOSIS; KYPHOTIC DEFORMITY; POSTERIOR APPROACH